HUBUNGAN ANTARA CAREER RELATED PARENT SUPPORT DENGAN CAREER DECISION SELF EFFICACY PADA SISWA SMP KRISTEN 2 SALATIGA - Gunawan Duwila; S.A Kristianingsih (Jurnal Cakrawala Ilmiah, 2024)
Humans always have hopes and dreams. These hopes and dreams can be realized in various processes where the process begins when the child goes through the education period. Individuals are guided to go to school so that they can get an education that supports them in the future. This process can be done by preparing to adjust to work, the world of work, and changing jobs or by leaving the world of work. the purpose of this study is to determine the relationship between parental social support for career decisions and self-efficacy in making career decisions for junior high school students.This research is a study with correlational quantitative methods. The results of this study found that career decision making self-efficacy significantly influenced career related parental support significantly in Christian Junior High School 2 Salatiga students.